Rational allocation of attention in decision-making - Stefanie Yvonne Schmitt (Bamberg University, Bamberg Economic Research Group (BERG), 2016)
This paper proposes a model of attention allocation in decision-making. Attention has various definitions across the literature. Here, I understand attention as selecting information for costly processing. The paper investigates how an agent rationally allocates attention. The resulting attention allocation is context-dependent and influences choice quality. Next to inattention, two strategies of allocating attention prevail. These strategies share similarities with bottom-up and top-down attention - concepts reported in the psychological literature. Exploring firms' strategic considerations reveals an incentive for firms to produce high quality and highlight quality, if consumers expect low quality, and to exploit consumers by producing low quality and shrouding quality, if agents expect high quality.
Keywords: D10; D03; D81; D83; L15; 330; rational attention; information-processing; decision-making; shrouding